Internal hernia following laparoendoscopic single site surgery: a case report - Anas Aboalsamh; Yousef Bassi; Rakan K. Alhabib; Ahmed Khalaf; Toufik Jouhar; Muhammed Jameel; Najib Kadi; Ahmed Al Hashemy; Ghaleb Aboalsamh (BMC Nephrology)
Abstract Laparoscopic donor nephrectomy was introduced in 1995 as a means of minimally invasive surgeries that entail kidney extraction from healthy individuals. Since then, it has widely overtaken the traditional open surgical approaches, especially in live donor nephrectomy procedures worldwide. Laparoendoscopic single-site surgery is considered a more optimized surgical approach utilizing a single incision instead of four. Various studies have scrutinized many of the risk factors related to such surgeries, most commonly: vascular problems, intraoperative organ injury, and postoperative ileus. Other rare complications have not been thoroughly explored due to their decreased prevalence. Internal hernias are considered a rare complication of laparoendoscopic single-site surgery with dangerous repercussions ranging from bowel obstruction to ischemia, and necrosis. Our study presents a rare case of a trans-mesenteric internal hernia following laparoendoscopic single-site surgery. The patient was relatively healthy with no serious medical conditions. However, the past medical history did record a diagnosis of irritable bowel syndrome a few years back. Knowing that the occurrence of internal hernias is infrequent, we recommend that mesenteric defects be taken seriously to avoid the risk of internal hernias and their complications.